An AI and virtual reality-based computational model to simulate olfactory responses: proposing a research strategy - Ferreira, Yasmim Thasla Santos; Siqueira, Alexandre Gomes de; Andrade, Carolina Horta; Winkler, Ingrid (Anais Estendidos do Simpósio de Realidade Virtual e Aumentada (SVR), 2024)
The combination of artificial intelligence and immersive technologies has the potential of enhancing olfactory experiences. This work proposes a research strategy for developing design guidelines for a computational model that integrates artificial intelligence and virtual reality technologies to simulate olfactory responses. We will follow the design science research approach, which will include a literature review, the development of design guidelines, and their evaluation. By leveraging machine learning algorithms and sensory data, the project seeks to optimize the perception and delivery of scents. The outcomes will contribute to creating more personalized and immersive olfactory experiences, potentially transforming industries such as perfumery and virtual reality.